EFEKTIVITAS METODE BERCERITA DENGAN BUKU CERITA BERGAMBAR BERBASIS ISLAM DALAM MEMBINA AKHLAK SISWA SDIT BUNAYYA PADANGSIDIMPUAN - NURSYAIDAH NURSYAIDAH (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Attitude is the most important aspect in human life because it relates to all the action and human character like good character or bad character with Allah and human. Attitude is one of the three basic from Islam religion and also has important position. So using the telling the story in Islam method can improve the students’ attitude. Formulation of this research is how is the learning process done by using telling stories method of Islamic pictured book in teaching attitude of students in SDIT Bunayya Padangsidimpuan? How effective of telling stories method with Islamic picture book in teaching attitude for students in SDIT Bunayya Padangsidimpuan? The result of research in learning process use telling stories method of Islamic pictured book in teaching attitude of students in SDIT Bunayya Padangsidimpuan with values of religion by the aims can teaching the students’ attitude. Actually, telling stories method of Islamic pictured book can teach the students’ attitude because by telling the story method, the students can understand what the teacher said.